New Aspects of Neurotransmitter Release and Exocytosis: Rho-Kinase-Dependent Myristoylated Alanine-Rich C-Kinase Substrate Phosphorylation and Regulation of NeurofilamentStructure in Neuronal Cells - Yasuharu Sasaki (Elsevier, 2003)
ABSTRACT: Myristoylated alanine-rich C-kinase substrate (MARCKS) is an actin-binding protein whose function may be regulated by the phosphorylation of multiple sites, in which the phosphorylation site domain (PSD) is recognized to have three or four PKC-dependent sites. Recently, it is considered that MARCKS is implicated in some neuronal functions, such as synaptic vesicle trafficking and neurotransmitter release, through regulation of the actin-containing cytoskeletal structure; this is based on the experimental results with short-term or prolonged pretreatment with phorbol esters and treatment by protein kinase C (PKC) inhibitor. However, the precise molecular mechanism is yet obscure. Recently, we have demonstrated that MARCKS is phosphorylated at Ser159 in PSD by Rho-kinase in vitro and that the phosphorylation occurred in neuronal cells upon stimulation with lysophosphatidic acid (LPA), and its phosphorylation was inhibited by a novel and specific Rho-kinase inhibitor, H-1152. Our results allow us to speculate that a preinflammatory substance, such as LPA, interleukin 1-β, and bradykinin, augments MARCKS phosphorylation in a novel signal transduction pathway besides the PKC-involved one, and thereby induces the release of a neurotransmitter through a reorganization of actincontaining microfilaments at the cell periphery, the so-called "active zone". In this section, I address a novel mechanism for MARCKS phosphorylation and its related cellular function.